Factors influencing the end‐diastolic vortex assessed by using vector flow mapping. Issue 9 (8th August 2019) - Zhang, Xiaoxia; Niu, Jun; Wu, Ling; Li, Qiaozhen; Han, Yu; Li, Yiwei; Wu, Xiaoyi; Che, Xinyi; Li, Zhiguo; Ma, Na; Zhang, Haibin
Abstract: Objectives: The purpose of this study was to assess the factors influencing the late diastolic vortex in normal and abnormal ventricles. Methods: Color Doppler data in left ventricle (LV) were acquired from apical long‐axis view and analyzed using vector flow mapping in 57 patients with coronary artery disease, 57 patients with dilated cardiomyopathy, and 53 healthy volunteers. Results: In normals, corrected area and flux of the end‐diastolic vortex were positively correlated with transmitral A velocity and heart rate. Subjects with E / A <1 had higher vortex flux than those with E / A >1. Heart rate was the only independent predictor of corrected vortex area ( R 2  =  .170, P =  .004), and transmitral A velocity and heart rate were the independent predictors of corrected vortex flux ( R 2  =  .490, P <  .001). Patients with various mitral filling patterns showed significant differences in vortex area and flux. The vortex area and flux were positively correlated with transmitral i velocity and a ′. Transmitral A velocity was the only independent predictor of corrected vortex area ( R 2  =  .180, P <  .001), while transmitral A velocity, heart rate, LV end‐systolic short diameter, and end‐diastolic long diameter were the independent determinants of corrected vortex flux ( R 2  =  .593, P <  .001). Conclusions: The end‐diastolic vortex is formed and mainly affected by the late LV filling. The compensatory atrial contraction may enhance the end‐diastolic vortex that facilitates coupling between diastole and systole. LV size can influence the end‐diastolic vortex in patients with LV dysfunction and enlargement.